2006
DOI: 10.1590/s1415-52732006000600003
|View full text |Cite
|
Sign up to set email alerts
|

Índice de qualidade da dieta de adolescentes residentes no distrito do Butantã, município de São Paulo, Brasil

Abstract: OBJETIVO: Avaliar o índice de qualidade da dieta de adolescentes residentes no Distrito do Butantã do município de São Paulo, SP. MÉTODOS: Estudo transversal de base populacional com uma amostra de 437 adolescentes, de ambos os sexos, com idade entre 12 e 19 anos. Foram obtidas amostras probabilísticas em dois estágios, setor censitário e domicílio, da área estudada. O consumo alimentar foi medido pelo método recordatório de 24 horas e a qualidade da dieta avaliada pelo Índice de Qualidade da Dieta adaptado pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
14
1
16

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 14 publications
7
14
1
16
Order By: Relevance
“…The association between parents' education level and FV intake was also found by other studies 9,31 . Godoy et al 31 studied 437 male and female adolescents from the neighborhood of Butantã, municipality of São Paulo, aged 12 to 19 years and found that FV intake increased with the education level of the family head.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The association between parents' education level and FV intake was also found by other studies 9,31 . Godoy et al 31 studied 437 male and female adolescents from the neighborhood of Butantã, municipality of São Paulo, aged 12 to 19 years and found that FV intake increased with the education level of the family head.…”
Section: Discussionsupporting
confidence: 84%
“…Godoy et al 31 studied 437 male and female adolescents from the neighborhood of Butantã, municipality of São Paulo, aged 12 to 19 years and found that FV intake increased with the education level of the family head. The authors concluded that higher education level leads to better food-related knowledge, increasing food variety and promoting higher FV intake.…”
Section: Discussionmentioning
confidence: 99%
“…North American studies have found higher diet quality among women 20,21 . In Brazil studies that evaluated diet quality using the HEI or BHEI-R have found worse eating habits in adolescents 22,23 and adult females 24 . The fact that females have better diet quality could be the result of several factors, such as increased attention to health and signs of disease, increased concern with body image, the role of being the family caregiver and generally having the responsibility of selecting and preparing meals, as well as the lower consumption of food away from home 25,26 ; women also have more careful attitude towards their health than men 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Given the high intake of processed foods by children and adolescents [25][26][27][28] , the replacement of meals by snacks 24,29 and the high sodium contents of the study foods, one can infer that they contribute to a high sodium intake.…”
Section: Discussionmentioning
confidence: 99%
“…Since the consumption of processed foods by children and adolescents increases because of women working outside the home, greater convenience, quick preparation, durability and acceptance 26 , peer influence, higher purchase power, habit of eating out 27 , and advertising and marketing 25,28 , asking the food industry to reduce sodium content of their products is considered more effective than asking people to reduce the consumption of these products 33 .…”
Section: Discussionmentioning
confidence: 99%